Comparison of upper extremity function, pain, and tactile sense between the uneffected side of hemiparetic patients and healthy subjects - Balci, Nilay Çömük; Doğru Hüzmeli, Esra; Aytar, Aydan; Gokmen, Ozge; Depreli, Ozde (Society of Physical Therapy Science (Rigaku Ryoho Kagakugakkai) inui@ipec-pub.co.jp, 2016)
[Purpose] The aim of this study was to compare the unaffected upper extremity of patients with hemiparesis with that of healthy subjects in terms of function, pain, and tactile sense. [Subjects and Methods] Upper extremity evaluation parameters of 20 patients with hemiparesis were compared with an age-matched control group of 20 healthy subjects. A shorter version of the Disability of Arm and Shoulder Questionnaire, Upper Extremity Functional Index, and Simple Shoulder Test were used to evaluate the upper extremity functionality. The Visual Analog Scale was used to measure pain severity at rest, at night, and during activity. Tactile sensation levels were assessed by Semmes-Weinstein monofilaments at four palmar areas. [Results] A statistically significant difference was found in the upper extremity functionality between the groups. Pain severity at rest was significantly higher in the hemiparetic group. There was no significant difference in night and activity pain severities or tactile sensation levels between the groups. [Conclusion] According to our results, the unaffected side of patients with hemiparesis differs in functionality and pain at rest compared with that of healthy persons. Studies with larger sample size and various evaluation tests are needed to further investigate the unaffected side of patients with hemiparesis. © 2016 The Society of Physical Therapy Science.
Keywords: Hemiplegia; Sensation; Upper extremity